Clinical characteristics of the first three waves of hospitalised patients with COVID-19 in Japan prior to the widespread use of vaccination: a nationwide observational study - Nobuaki Matsunaga; Kayoko Hayakawa; Yusuke Asai; Shinya Tsuzuki; Mari Terada; Setsuko Suzuki; Hiroshi Ohtsu; Koji Kitajima; Ako Toyoda; Kumiko Suzuki; Michiyo Suzuki; Sho Saito; et al. (Elsevier, 2022)
Summary: Background: Before widespread coronavirus disease (COVID-19) vaccinations, Japan experienced three COVID-19 epidemic waves. This study aimed to evaluate the characteristics of hospitalised COVID-19 patients and reveal temporal changes. Methods: This study included 33,554 hospitalised patients with COVID-19 from 553 healthcare facilities. Data were analysed by age group and epidemic wave (first wave, 01/01/2020-05/31/2020; second wave, 06/01/2020-10/31/2020; and third wave, 11/01/2020-03/31/2021). Findings: By age group, 3% (under 18), 22% (young), 34% (middle-aged), and 41% (older patients) were aged 0-17, 18-39, 40-64, and >65 years; while 16%, 35%, and 49% were in the first, second, and third wave, respectively. The patients' overall median age (58 years; interquartile range, 39-74) was lowest and highest during the second and third waves, respectively. The frequency of any comorbidity was lowest and highest during the second (44·5%) and third (63·6%) waves, respectively. The symptoms at admission and exposure history differed considerably with age. The overall case fatality rate (5%) was highest among older patients (11·4%). Case fatality rate was highest and lowest during the first (7·3%) and second (2·8%) waves, respectively. Medication use changed over time. Interpretation: Although the overall case fatality rate remained relatively low, it was more than twice as high among older patients. After adjusting for age and comorbidities, the risk of death was highest in the first wave. Funding: This work was supported by the Ministry of Health, Labour and Welfare "Research on Emerging and Re-emerging Infectious Diseases and Immunization" 19HA1003].